« L’avant-guerre » des guerres de Religion, d’après les lettres historiques d’Etienne Pasquier - David El Kenz (Les Dossiers du GRIHL)
The pre-war period of the French Religious wars according to Étienne Pasquier’s historical-political letters. What is a period of "pre-war"? The question is a methodological challenge because it implies a finalist vision of history. It is all more complex when it is focused on religious wars (1562-1598), a French civil war, because the opening of the conflict was not official. To study these premises, this paper is based on Étienne Pasquier’s correspondence, a Parisian lawyer and humanist. Pasquier relates the events of the winter 1561-1562 which have preceded the armed conflict between religious parties.His interpretation of civil violence in the capital opposes religious passion and public regulation. Pasquier’s personal experience, his socio-political position and his involvement explain such an understanding of the period. They build the standard of the pre-war vision. On the one hand, high sensitivy to the religious passion and on the other, waiting hopelessly on the Crown remedies. The Pasquier’s correspondence reveals the inevitability of the disintegration of state.